IKHBĀR AL-QUR’ĀN ‘AN AL-MAZĀYĀ WA AL-KHAṢAIṢ FĪ ‘ĀLAM AL-NAML: Dirāsah ‘alā al-I’jāz al-‘Ilmī fī sūrat an-Naml - Sujiat Zubaidi Saleh; Abdul Rohman; Amir Hidayatullah; Amir Reza Kusuma (QOF, 2021)
Al-Quran as the miracle of The Prophet certainly has excellences that cannot be imitated by mere mortal. One of them is its scientific side of the miracle where al-Quran tells the scientific facts that cannot be understood by the sciences of the era of prophecy and just be proven by technology of modern era. This article revealed the scientific miracle of al-Quran about the life of the ants that includes their characteristics, uniqueness, and communication system with the colony and other animals. It is shown in surah an-Naml verse 18. Therefore, the researchers explained it with three key questions: 1) Why does it use collective pronoun (ḍamīr jama’ ‘uqalā) to refer to the ants? 2) What is the characteristic of the ants? 3) What are the special languages of the ants? The researchers used analytic descriptive method through researching interpretations that are related to the verse, both from classic interpreters or the contemporary ones, especially the scientific interpretations. Arguments were delivered with some explicit explanation from the experts of zoology studies. This research concluded that al-Quran is parallel to recent modern scientific discovery about ants, based on the diction, pronoun usage, and the context. This is the real proof that al-Qur’an is absolute revelation of Allah to the illiterate Prophet.